计算(x+2)(x-3)-(x-6)(x-1)=0
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 08:18:47
计算(x+2)(x-3)-(x-6)(x-1)=0计算(x+2)(x-3)-(x-6)(x-1)=0计算(x+2)(x-3)-(x-6)(x-1)=0(x+2)(x-3)-(x-6)(x-1)=0x^
计算(x+2)(x-3)-(x-6)(x-1)=0
计算(x+2)(x-3)-(x-6)(x-1)=0
计算(x+2)(x-3)-(x-6)(x-1)=0
(x+2)(x-3)-(x-6)(x-1)=0
x^2-x-6-(x^2-7x+6)=0
6x-12=0
x=2
x=2
x=2
展开化简得
6x-12=0
x=2
x/x-3-5x/x^2-x-6计算
计算:x/x-2 - 5x/x²-x-6计算:x/x-3 - 5x/x²-x-6
计算:[(x^2 - 4)/(x^2 - x - 6) + (x+2)/(x-3)] / (x+1)/(x-3)
计算:(x+1)(x-2)(x-3)(x-6)
计算:(x+2)/(x^2 - x - 6) + 2x/(x^2 - 3x) - x/(x^2 - 6x + 9)
计算 2+x+3/x-1*x^2-2x+1/x^2+6x+9
x^2+x-6分之x^2+3x-x^2-4分之x+2计算
计算(x-2)(x-3)+2(x+6)(x-5)-3(x平方-7x+13)
计算x^2-5x+6/x^2-1/x^2+x/x-3
(x-6)(x的平方+x+1)-x(2x+1)(3x-1)计算
计算(x*x+4x+5)/(x+2)-(x*x+6x+10)/(x+3)+1
x(x-2)(2x-3)计算
计算: (x+3)(x²-x-2)
计算 (x+3)(x²-x-2)
2x*4x-3x计算
计算:(-x^4)^3-(x^2)^6
*-----------------------------------------------*| 6 4 X | 8 X X | X X 5 || X X X | X X X | X 7 8 || X X X | X X X | X X X ||---------------+---------------+--------------- || X X X | X X X | 5 1 X || X X X | X 6 X | X X X || 8 X X | 3 5 X | 2 X X ||
x(x*x-6x-9)-x(x*x-8x-15)+2x(3-x)